Microcontroller based smart fan system - Abd. Ghani, Muhammad Khairi (2007)
This project will present the design, construction, development, control and evaluation of an automatic switching speed electric fan. This further step of an intelligent electric fans than before that using “intelligent technology’’ such sensing the sound of clapping and functioning by analog circuit relay from the lowest to the highest speed clapping by clapping. The microcontroller base automatic fan system presented in this project is required to fulfill the requirement of technologies “tomorrow will be more advanced than today”. The electric fan automatically switches the speed according to the environment temperature changes. This electric fan system contains combination of sensor, controller, driver and motor with integration of embedded controlled programming which means in this case using MC68HC11A1 as the main controller. This project also presents the expected performance of the automatic fan system, construction of hardware and software development to gather the performance data. Finally, this system performance will be evaluated by comparing performance data to the theoretical.